Penerapan Analisa Cost Benefit Pada Sistem Informasi Persediaan Barang ATK Guna Mempermudah Pemeriksaan Stok Barang - Dewi, Yumi Novita; Octavianil, Dea (Infotek: Jurnal Informatika dan Teknologi, 2024)
Adinda Shop is a shop that provides various office and school stationery equipment. This shop stands in a strategic location because across the road from the shop is a state high school. The problem that occurs is that the storage of incoming and outgoing goods is still in the form of archives, resulting in a buildup of data. And reports are only made based on the number of opinions obtained in a day. Therefore, the system that the author will create is WEB-based regarding the inventory of goods in this company. With the problems that exist at Toko Adinda, the research method used is the RAD method. And with this system, it is hoped that it will be beneficial for the company by proving it using Cost Benefit Analysis. And after the analysis, the result was 1.14, which stated that it was feasible for this system to be created. This system is applied to process incoming and outgoing goods to make it easier for companies to see the amount of stock, and making reports makes it easier for the company